Evidence of the miniband formation in InGaAsP/InP superlattices - Pusep, Yu A. (2006)
The formation of the miniband electron energy structure was explored in doped InGaAs/InP superlattices with different periods. The analysis of the Raman data allowed us to conclude that in spite of the defect structure of the layers constituting the superlattices, their super-periodicity was well defined. The quantitative proof of the conditions for break-down of the Raman selection rules is presented: the emergence of the selection rules of the coupled plasmon-LO phonon vibrations was demonstrated to occur due to the increase of their coherence lengths. In addition, the expected anisotropy of the effective electron masses was found by high-field magnetoresistance.